ELITE Magazine : The IEM-SAFE UNIMAS Student Section 2021-2022, 2nd Edition - Kasumawati, Lias; Siti Noor Linda, Taib; Ervina, Junaidi; Hani Hazwani, Perlis; Brenda Leong, Pei Yen (UNIMAS Publisher, 2023)
IEM-SAFE ELITE Magazine presents the activities organized by the IEM-SAFE UNIMAS Student Section. This is the second edition magazine of The IEM-SAFE UNIMAS Student Section, edited by Exco Media & Publicity. It consists of the information on the activities conducted by the IEM-SAFE UNIMAS Student Section. IEM-SAFE ELITE Magazine promotes the IEM-SAFE UNIMAS Student Section and its activities to the UNIMAS community, especially the Faculty of Engineering staff and students.